2021
DOI: 10.1111/hsc.13372
|View full text |Cite
|
Sign up to set email alerts
|

Project ECHO: Enhancing palliative care for primary care occupational therapists and physiotherapists in Ireland

Abstract: Project ECHO (Extension for Community Healthcare Outcomes) uses videoconferencing technology to support and train healthcare professionals (HCPs) remotely. A 4‐month fortnightly ECHO programme was developed and implemented to enhance palliative care provision by primary care therapists. Teaching and case‐based discussions were facilitated by palliative care specialists. A mixed‐methods cohort study was used to evaluate the project. ECHO participants completed pre‐ and post‐programme questionnaires regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(43 reference statements)
3
10
0
1
Order By: Relevance
“…This study findings highlight the improvement in knowledge of ASHAs related to oral health and palliative care post-ECHO training. An improvement in knowledge has also been observed in other studies that have evaluated ECHO telementoring interventions in cancer screening [ 36 ], palliative care [ 37 , 38 ], HIV [ 39 ], and chronic pain [ 40 ] In this study, ASHAs reported poor knowledge of the immunisation schedule for a newborn as well as the confidence to record and track immunisation in the community even after the ECHO training. A critical function of ASHAs is to assist ANMs or nurses with all immunisation activities [ 41 ].…”
Section: Discussionsupporting
confidence: 76%
“…This study findings highlight the improvement in knowledge of ASHAs related to oral health and palliative care post-ECHO training. An improvement in knowledge has also been observed in other studies that have evaluated ECHO telementoring interventions in cancer screening [ 36 ], palliative care [ 37 , 38 ], HIV [ 39 ], and chronic pain [ 40 ] In this study, ASHAs reported poor knowledge of the immunisation schedule for a newborn as well as the confidence to record and track immunisation in the community even after the ECHO training. A critical function of ASHAs is to assist ANMs or nurses with all immunisation activities [ 41 ].…”
Section: Discussionsupporting
confidence: 76%
“…Undergraduate curricula should include topics related to (1) discontinuation of unnecessary medical procedures and (2) management of sedatives, analgesics, and muscle relaxants in PC patients. Case-based learning and short didactic lectures have demonstrated the potential to expand and distribute knowledge and skills in the field of PC [ 56 ]. They have significantly increased physicians’ confidence in practising PC in the Thai context [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Od tego czasu ukazały się jeszcze dwie odsłony tego szkolenia (wszystkie finansowane przez Health Service Executive), a uczestnicy zwrócili uwagę przede wszystkim na zwiększenie swojego zasobu wiedzy z zakresu terapii bólu i Advace Care Planning [18]. Pozytywnie został również odebrany kurs skierowany do terapeutów zajęciowych oraz fizjoterapeutów [19].…”
Section: Fundament 3 Traktowanie Opieki Paliatywnej Jako Standardoweg...unclassified